Outcomes and Management of Head and Neck Cancer at a South Indian Cancer Centre: A Retrospective Study - Nagarajan, Murugaiyan; Banu, Ramesh; Shrividhya, Ananthakrishnan; Chellapandian, Thirumalai Palanichamy; Rajkumar, Arumugham; Mohanraj, Ramaswamy (Indian Journal of Medical and Paediatric Oncology, 2022)
Introduction Head and neck cancers are one of the most common cancers in the Indian subcontinent. The trends of these cancers worldwide have drastically changed over the past 15 years. In spite of all the new technology and timely diagnosis, the treatment of these cancers is still a challenge. These cancers still continue to be a significant cause of morbidity and mortality worldwide.Objectives To identify different patterns of care received by patients with primary head and neck cancer in a single center and analyze the outcomes of the different patterns of care received by these patients in terms of overall survival and disease-free survival.Materials and Methods We included 707 patients with primary head and neck cancer registered and treated in our institution from January 2015 to December 2017. The demographic details of the patient, treatment received, and outcomes of treatment were collected retrospectively from our hospital's medical registry. Descriptive analysis was performed by calculating mean and standard deviation for quantitative variables, whereas frequency and proportion were calculated for categorical variables. The mean/median overall survival and recurrence-free survival were compared across various explanatory parameters using log rank–test. A p-value < 0.05 was considered statistically significant.Results A total of 707 patients were included in the final analysis. The median age of presentation was 60 years. In total, 50% of patients presented with stage IV disease at diagnosis and 78% had a history of smoking or other tobacco use. Oral cavity was the most common primary site. Concurrent chemotherapy with radiation therapy was the most common modality of treatment used in 49% of patients: RT was the common modality of treatment in 21% patients. Fourteen percent patients were treated by only surgery. All patients who underwent treatment were included for survival analysis, which showed that the median overall survival time was 42 months (34–49 months). The median duration of disease free-survival time was 37 months (30–43 months).Conclusion In our study, most patients presented with locally advanced disease. Multimodality treatment yielded better results. Based on our study, in early-stage cancer, where single modality treatment was used, adjuvant therapy should be tailored based on nomogram.
Keywords: head and neck cancer; survival; epidemiology; patterns of care; outcome; radiotherapy; chemotherapy